2018
DOI: 10.3389/fnagi.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Fungi and Bacteria in Brain Tissue From Elderly Persons and Patients With Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the leading cause of dementia in elderly people. The etiology of this disease remains a matter of intensive research in many laboratories. We have advanced the idea that disseminated fungal infection contributes to the etiology of AD. Thus, we have demonstrated that fungal proteins and DNA are present in nervous tissue from AD patients. More recently, we have reported that bacterial infections can accompany these mycoses, suggesting that polymicrobial infections exist in AD brains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 84 publications
6
152
1
2
Order By: Relevance
“…Studies have demonstrated the presence of microorganisms in brains of both AD patients and healthy controls. However, increased LPS levels (Zhan et al, 2016; and an increased presence of several bacteria and fungi, including some gut commensals, were observed in brains of AD patients compared to controls (Mawanda and Wallace, 2013;Pisa et al, 2017;Alonso et al, 2018;Dominy et al, 2019). The presence of bacterial LPS or endotoxin-mediated inflammation contributes to amyloid neurotoxicity .…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…Studies have demonstrated the presence of microorganisms in brains of both AD patients and healthy controls. However, increased LPS levels (Zhan et al, 2016; and an increased presence of several bacteria and fungi, including some gut commensals, were observed in brains of AD patients compared to controls (Mawanda and Wallace, 2013;Pisa et al, 2017;Alonso et al, 2018;Dominy et al, 2019). The presence of bacterial LPS or endotoxin-mediated inflammation contributes to amyloid neurotoxicity .…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…adding mathematical models that describe how molecular changes alter population activity -so called cause--and--effect models. We will focus here on the disrupted inhibitory function of interneurons and consecutive hyperexcitability caused by Abeta -while we are aware of various other factors with potential roles for AD aetiology, such as vascular changes (19--21), neuroinflammation (22--25), genetics (26--28), environmental factors (29,30) and concomitant proteinopathies others than Abeta pathology (31,32). Beside Abeta there is a second molecular hallmark associated with the pathogenesis of AD: the phosphorylated Tau 'tubulin--associated unit' protein (8,33,34) which contributes to microtubule stability in the neural cytoskeleton (34).…”
mentioning
confidence: 99%
“…Several metabolic functions like biosynthesis of secondary metabolites and amino acid, carbohydrate, energy, lipid, cofactors and vitamins, terpenoids and polyketides, nucleotide and xenobiotic biodegradation and metabolism were observed in the analysis. There are several reports on occurrence of fungi in different regions of brain tissues and blood vessels, recovered from the patients suffering Alzheimer’s disease and Parkinson’s disease (Pisa et al 2015; Alonso et al 2017, 2018). Addressing this aspect, we emphasized our analysis towards the functional profile of the autochthonous and the allochthonous fungal communities.…”
Section: Discussionmentioning
confidence: 99%